Theoretical investigation of the combustion performance of ammonia/hydrogen mixtures on a marine diesel engine - Wang, Yang; Zhou, Xiaohu; Liu, Long (International journal of hydrogen energy, 2021)
Ammonia is a good hydrogen carrier and can be well combined with hydrogen for combustion. The combustion performance of the mixtures of ammonia and hydrogen in a medium-speed marine diesel engine was investigated theoretically. The HCCI combustion mode was selected for reducing thermal-NOx production. The start fire characteristic of the NH3–H2 mixtures was studied under different equivalence ratio, hydrogen-doped ratio, and intake air temperature and pressure. Then, the combustion performance of the NH3–H2 mixtures (doping 30% hydrogen) was analyzed at a typical operation condition of engine. The addition hydrogen improved the laminar flame velocity of ammonia, and affected the NOx emission. For the medium-speed marine engine fueled with NH3–H2, reducing combustion temperature, introducing EGR and combining with post-treatment technology would be a feasible scheme to reduce NOx emission. •The start fire characteristic of the NH3–H2 mixtures was studied.•The combustion performance of the NH3–H2 mixtures was analyzed.•The addition hydrogen improved the laminar flame velocity of ammonia.•A scheme to completely eliminate NOx emission was proposed.